Analysis of the existing information of La Carpio informal settlement, Roble Norte sector, to create the basis for future research in fire safety. - Guevara-Arce, Sara María (Instituto Tecnológico de Costa Rica, 2020)
In Costa Rica, more than 220,000 people live in informal settlements, under a situation of vulnerability and risk (INEC, 2011). There is a global tendency for population growth, this growth will not be distributed equally geographically, it will mostly affect low to low-middle income countries (UN,2018). This population rising will foster the increase of people inhabiting informal settlements or will trigger the creation of new ones. Fire risk is another subject affecting these kinds of settlements, proper investigation regarding fire safety in informal settlements has been disregarded by the Costa Rican researchers. This research focusses its attention in La Carpio informal settlement, taking as a sample the Roble Norte sector. It collects the available data regarding quantitative and qualitative aspects of the settlement, also gathers sociodemographic data and fire records with the intention of performing the data and fire risk analysis for this community. This document has the main intention of being a basis for future investigation, boosting researchers to get involved in topics related to fire safety or update databases which help decisions making for problem-solving in informal communities.

En Costa Rica, más de 220,000 personas viven en asentamientos informales, en situación de vulnerabilidad y riesgo (INEC, 2011). Existe una tendencia global de crecimiento poblacional, este crecimiento no será distribuido de manera equitativa geográficamente, ya que los países de ingresos bajos a medio bajos serán los más afectados (UN, 2018). Este crecimiento poblacional fomentará el aumento de personas habitando en asentamientos informales o desencadenará la creación de nuevos asentamientos. El riesgo de incendios es otro tema afectando estas comunidades, investigación relacionada con seguridad contra incendios en asentamientos informales ha sido ignorado por los investigadores costarricenses. Por lo anterior, esta investigación centra su atención en el asentamiento informal La Carpio, tomando a su vez como muestra el sector Roble Norte. Aquí se recolectan los datos disponibles en relación con características cuantitativas y cualitativas del asentamiento, además información sociodemográfica y registros de incendio con la intención de realizar el análisis de datos y de riesgo de incendios de esta comunidad. Este documento tiene como principal intención ser una base para futuras investigaciones, impulsando a los investigadores a involucrarse con temas relacionados con la seguridad contra incendios o la actualización de bases de datos, que puedan ayudar a tomar decisiones para la resolución de problemas en comunidades informales.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2020.
Keywords: Análisis de la información; Seguridad contra incendios; Asentamiento informal; Bases de datos; Riesgo de incendio; Analysis of the information; Fire safety; Informal settlement; Databases; Fire risk